2020
DOI: 10.3390/v12020174
|View full text |Cite
|
Sign up to set email alerts
|

ABCE1 Acts as a Positive Regulator of Exogenous RNA Decay

Abstract: The 2′-5′-oligoadenylate synthetase (OAS)/RNase L system protects hosts against pathogenic viruses through cleavage of the exogenous single-stranded RNA. In this system, an evolutionally conserved RNA quality control factor Dom34 (known as Pelota (Pelo) in higher eukaryotes) forms a surveillance complex with RNase L to recognize and eliminate the exogenous RNA in a manner dependent on translation. Here, we newly identified that ATP-binding cassette sub-family E member 1 (ABCE1), which is also known as RNase L … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 32 publications
(70 reference statements)
1
5
0
Order By: Relevance
“…It is not clear if transfected exogenous RNAs are processed differently from the endogenous RNAs cleaved in the cellular context and during viral infections. In line with other studies on RNase L activation, in our studies, the ligand 2-5A was delivered by complexing with lipid reagents, in contrast to the electroporation-mediated delivery used by Nogimori et al [ 40 ]. Furthermore, basal levels of OAS proteins and RNase L vary by cell types and are determinants of IFN induction during viral infection, including EMCV [ 64 ].…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…It is not clear if transfected exogenous RNAs are processed differently from the endogenous RNAs cleaved in the cellular context and during viral infections. In line with other studies on RNase L activation, in our studies, the ligand 2-5A was delivered by complexing with lipid reagents, in contrast to the electroporation-mediated delivery used by Nogimori et al [ 40 ]. Furthermore, basal levels of OAS proteins and RNase L vary by cell types and are determinants of IFN induction during viral infection, including EMCV [ 64 ].…”
Section: Discussionsupporting
confidence: 75%
“…The effects of ABCE1 on inhibiting RNase L is specific as cells lacking both proteins show no nucleolytic activity. In contrast, another recent study showed the interaction of ABCE1 with Dom34 (Pelota) and RNase L to function as a positive regulator of exogenous RNA decay [ 40 ]. It is not clear if transfected exogenous RNAs are processed differently from the endogenous RNAs cleaved in the cellular context and during viral infections.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Next, we wanted to assess what changes directly result from the global RNA cleavage that occurs after RNase L activation. RNase L is known to interact with several proteins, including those that make up the cytoskeleton and the nucleopore complex (Bisbal et al, 1995; Burke et al, 2021; Le Roy et al, 2005; Nogimori et al, 2019; Nogimori et al, 2020; Tnani et al, 1998). Thus, it is possible that some of the observed changes upon RNase L activation and dimerization arise from functional protein-protein interactions and not RNA cleavage.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies suggest the action of ABCE1 together with RNAse L to eliminate exogenous RNA [ 96 ]. Taken together, the present data provide evidence for the regulation of the 2’-5’ OAS pathway independent of ABCE1 and RNAse L, providing support for a key role of this pathway in the immune response in infections by LbLRV1+ parasites.…”
Section: Discussionmentioning
confidence: 99%